A Systematic Review and Meta‐Analysis of Metolazone Compared to Chlorothiazide for Treatment of Acute Decompensated Heart Failure. Issue 9 (7th August 2020) - Steuber, Taylor D.; Janzen, Kristin M.; Howard, Meredith L.
Abstract : Treatment of volume overload in the setting of acute decompensated heart failure (ADHF) is typically achieved through the use of loop diuretics. While they are highly effective, some patients may develop loop diuretic resistance. One strategy to overcome this scenario includes sequential nephron blockade with a thiazide‐type diuretic; however, it is unknown which thiazide‐type diuretic used in this setting is most effective. A systematic review and meta‐analysis were performed to compare the efficacy and safety of chlorothiazide with metolazone as add‐on therapy in the setting of loop diuretic resistance for the treatment of ADHF. Literature searches were conducted through PubMed, Google Scholar, and Science Direct from inception through February 2020 using the following search terms alone or in combination: metolazone, chlorothiazide, acute decompensated heart failure, loop diuretic, and urine output. All English‐language prospective and retrospective trials and abstracts comparing metolazone to chlorothiazide for the treatment of ADHF were evaluated. Studies were included if they analyzed urine output for at least 24 hours in patients with ADHF. Meta‐analysis was conducted to evaluate pooled effect size by using a random‐effect model. Primary outcomes included net and total urine output. Secondary outcomes included commonly reported safety outcomes. Four studies comparing the use of metolazone to chlorothiazide as an adjunct to loop diuretics to treat ADHF were included in the evaluation. Metolazone was as effective as chlorothiazide to augment loop diuretic therapy in ADHF in most studies with no pooled difference in net or total urine output. However, there were notable differences in baseline loop diuretic dosing, ejection fraction, renal function, race, and endpoint timing across studies. Adverse effects were commonly observed and included electrolyte abnormalities, change in renal function, and hypotension but were comparable between groups. Metolazone is as effective as chlorothiazide as add‐on to loop diuretics in treating ADHF without an increase in safety concerns.